IMPLICATIONS OF BURNOUT AND PERSON-JOB FIT ON JOB SATISFACTION AMONG EMPLOYEES OF THE EXTERNAL AFFAIRS SECURITY DIVISION AT PT. CPM PALU - Adrial L., Foster; Kornelius, Yoberth; Ibrahim, Andi Indriani; Palawa, Muh. Riswandi (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of burnout and person–job fit on employee job satisfaction at PT Citra Palu Mineral (CPM) Palu. A quantitative approach was employed using multiple linear regression analysis. The sample consisted of 46 employees from the External Affairs Security Division selected through saturated sampling. The findings reveal that burnout has a negative but insignificant effect on job satisfaction, whereas person–job fit has a positive and significant effect. Simultaneously, burnout and person–job fit significantly influence job satisfaction, indicating that alignment between employees and job characteristics plays a key role in enhancing satisfaction.